Representation of Islamic Ideology in the Discursive Practices: A Critical Review of ESL Classrooms at Undergraduate Level (Al Basirah, 2020)
The study focuses on the Islamic ideological discursive manifestationsin the second language multicultural classroom as to how they are enacted.The ESL classrooms involve the classroom participants in learning the nonnative language through the explanatory discourses as enacted by theirteachers. The classroom participants in any setting prefer their own sociallyconstructed religious values. Since, classroom is a constituent of the socialgrowing practices; the classroom approved practices contribute a substantialpart in developing and establishing social norms in terms of ideologicalpreferences. All the universities of the Islamabad were taken as the sites ofthe study where the undergraduate four-year English program is offered. Thestudy is a census enquiry where all the population (students) of the sites istaken as sample of the study for data collection. The data were collectedthrough, closed-ended questionnaires. It was found that the ideologies of thedominant groups are prevalent in the ESL undergraduate classroomsdiscursive practices. Although the classrooms have religious freedom;however, Islamic ideology prevails in terms of its practice and preference.In order to get plausible academic results in the ESL multiculturalclassroom, the teachers need to understand, perceive and sensitizethemselves to the cultural, ideological and social understanding of thestudents for a smooth academic process in the language classroom.
Keywords: Islamic Ideology, ESL Classroom, Discursive Practices, Dominant groups.